Regenerating public housing in Italy within the Next Generation EU fund. Learnings from a research-by-design experience in Bergamo (EAAE Annual Conference Proceedings, 2023)
In 2021 Italy launched a National Innovative Program for Housing Quality (PINQuA), enabled by the Next Generation EU instrument, and funded with 2,8 billion euros. By funding 159 projects, the program opens a new season for public housing in Italy after more than three decades of shrinking investment, a short season that will run out by 2026, largely centred on regenerating the existing public housing stock.